Autoantibody pathogenicity in a multifocal motor neuropathy induced pluripotent stem cell–derived model. Issue 1 (1st June 2016) - Harschnitz, Oliver; van den Berg, Leonard H.; Johansen, Lill Eva; Jansen, Marc D.; Kling, Sandra; Vieira de Sá, Renata; Vlam, Lotte; van Rheenen, Wouter; Karst, Henk; Wierenga, Corette J.; Pasterkamp, R. Jeroen; van der Pol, W. Ludo
Abstract : Objective: We investigated the pathogenicity of immunoglobulin M (IgM) anti‐GM1 antibodies in serum from patients with multifocal motor neuropathy (MMN) using human induced pluripotent stem cell (iPSC)‐derived motor neurons (MNs). Methods: iPSCs were generated from fibroblasts and differentiated into MNs. We studied the binding of IgM to MNs, their complement‐activating properties, and effects on structural integrity using fluorescence and electron microscopy. Live cell imaging was used to study effects of antibody binding on MNs in the presence and absence of complement. Results: IgM antibody binding to MNs was detected using sera from MMN patients with and without detectable anti‐GM1 IgM antibody titers in enzyme‐linked immunosorbent assay, but not with sera from (disease) controls. Competition and depletion experiments showed that antibodies specifically bound to GM1 on iPSC‐derived MNs. Binding of these antibodies disrupted calcium homeostasis by both complement‐dependent and complement‐independent pathways. MNs showed marked axonal damage after complement activation, and reduced antibody pathogenicity following treatment with immunoglobulin preparations. Interpretation: Our data provide evidence for the pathogenicity of anti‐GM1 IgM antibodies in MMN patients and link their presence to the clinical characteristics of axonal damage and immunoglobulin responsiveness. This iPSC‐derived disease model will facilitate diagnosis, studies on autoantibody pathogenicity, drug development, and screening in immune‐mediated neuropathies. Ann Neurol 2016;80:71–88